Hubungan Intensitas Menonton Tiktok Terhadap Motivasi Berolahraga Siswa Kelas IX SMP Negeri 2 Rancakalong - Alif Fikri Fikri; Indra Safari; Dewi Susilawati (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2026)
This study aimed to determine the relationship between the intensity of watching TikTok and students’ motivation to exercise at SMPN 2 Rancakalong. The research employed a correlational method with a quantitative approach. The sample consisted of 31 students selected using purposive sampling technique. Data were collected using a questionnaire that had been tested for validity and reliability. Data analysis was conducted using descriptive statistics, Spearman correlation test, and simple linear regression with the help of SPSS version 26. The results showed that there is a significant relationship between the intensity of watching TikTok and students’ motivation to exercise, with a correlation coefficient of 0.801 and a significance value of 0.000 < 0.05, indicating a very strong and positive relationship. In conclusion, the intensity of watching TikTok has a significant relationship with students’ motivation to exercise.   Keywords: Exercise Motivation, Intensity of Watching, Social Media, Students, Tiktok